2022
DOI: 10.3390/agronomy12051129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between the Photosynthetic Parameters of Two Avocado (Persea americana) Cultivars Reveals Natural Variation in Light Reactions in Response to Frost Stress

Abstract: Avocado is a commercially important fruit tree which is sold worldwide. Originating in subtropical regions of the South America, this species is now grown worldwide and is sometimes exposed to cold temperatures. Specifically, frost stress harms the crop yield and its quality. While it is known in general that the photosynthetic apparatus changes in response to cold conditions, there is still not much information regarding the photosynthetic apparatus response to sporadic frost stress. In this study, we tracked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In areas close to the equator, the length of the day does not seem to change significantly (YEANG, 2007), and as for solar radiation, Renner (2007) reported that when the sun passes directly over the equator twice a year, a bimodal cyclic change in the incoming solar radiation (insolation) is observed on these regions. point (WEIL et al, 2022). In this research, maximum PAR values above 2,000 µmol/m-2/s-1 were recorded and the average values observed were slightly less than 1,400 µmol/m-2/s-1 (Figure 9 A-B).…”
Section: Photosynthetically Active Radiation (Par)mentioning
confidence: 51%
See 2 more Smart Citations
“…In areas close to the equator, the length of the day does not seem to change significantly (YEANG, 2007), and as for solar radiation, Renner (2007) reported that when the sun passes directly over the equator twice a year, a bimodal cyclic change in the incoming solar radiation (insolation) is observed on these regions. point (WEIL et al, 2022). In this research, maximum PAR values above 2,000 µmol/m-2/s-1 were recorded and the average values observed were slightly less than 1,400 µmol/m-2/s-1 (Figure 9 A-B).…”
Section: Photosynthetically Active Radiation (Par)mentioning
confidence: 51%
“…While the three ecological avocado cultivars offer a wide range of adaptation to air temperature (WEIL et al, 2022), for the 'Hass' cultivar in particular, Garner and Lovatt (2016) found that under the southern Australia conditions, only the coldest (17/10°C) and hottest (37/30°C) treatments restricted growth and dry matter accumulation, while…”
Section: Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The light response of two avocado cultivars to sporadic frost stress can have negative results on crop yield and fruit quality, as stated in the study conducted by Weil et al [69]. The focus of the study was on the photosynthetic parameters of these avocado varieties, and the researchers examined their responses to frost stress in four instances both in the laboratory and in the field conditions.…”
Section: Risk Management and Yield In Avocado Cropsmentioning
confidence: 99%
“…Damage can range from burning of shoots and foliage, damage to flowering buds and fruits and even death of trees in more extreme cases (Witney & Arpaia, 1991;Mandemaker, 2008). Physiological and biochemical aspects of the response of avocado 'Hass' to chilling and frost/freezing have been studied (Joshi et al, 2020;Chung et al, 2022;Weil et al, 2022), focusing on photosynthetic performance, reactive oxygen species (ROS) and antioxidants. Possible horticultural means for mitigating frost damage in 'Hass' orchards include wind machines or highdensity shading nets (Lahak et al, 2024;Bar-Noy et al, 2019).…”
mentioning
confidence: 99%